A feasible CT feature to differentiate focal‐type autoimmune pancreatitis from pancreatic ductal adenocarcinoma - Chaobin He; Dailin Rong; Wanming Hu; Qian Cai; Qiuxia Yang; Yize Mao; Rong Zhang; Shengping Li; Yanchun Lv (Cancer Medicine, 2019)
Abstract Background To investigate whether the relative computed tomography (CT) value (rCT) of adjacent pancreatic parenchyma can distinguish focal‐type autoimmune pancreatitis (fAIP) from pancreatic ductal adenocarcinoma (PDAC). Methods A total of 13 patients with fAIP and 20 patients with PDAC were included in this study. The rCT was calculated as the ratio of the CT value of adjacent pancreatic parenchyma to that of muscle. The diagnostic performance of rCT for discriminating fAIP from PDAC was evaluated using receiver operating characteristic (ROC) analysis. Results Both fAIP and PDAC presented hyper‐fibrosis histologically and delayed enhancement on CT examination. Moreover, the pancreatic parenchyma of fAIP presented serious inflammation. The mean rCT of the parenchyma was significantly lower in fAIP than in PDAC in all phases. The best diagnostic performance of the rCT value was found in the pancreatic phase, with an area under the ROC curve of 0.912, while the areas under the ROC curve of the portal and delayed phases were 0.812 and 0.754, respectively. The optimal cut‐off value for distinguishing fAIP from PDAC was 1.62 in the pancreatic phase. Conclusions The rCT of the pancreatic parenchyma during the pancreatic phase may be a feasible CT feature for differentiating fAIP from PDAC.